Wafer-Scale Experimental Determination of Coupling and Loss for Photonic Integrated Circuit Design Optimisation - Daniel Schmid; René Eisermann; Anna Peczek; Georg Winzer; Lars Zimmermann; Stephan Krenek (Photonics)
We investigate integrated silicon ring resonators with regard to the influence of design parameters and intra-wafer variations. First, we show the effect of different ring radii and gaps between ring and bus waveguide on optical properties (peak width, finesse, Q factor, and extinction ratio), from which we calculate the resonators’ coupling and loss coefficients. The dependence on the gap of these properties is discussed at the wafer scale. Second, by incorporating the spectra of 2242 resonators from 59 nominally identical dies on a 200 mm wafer, we show how these properties depend on the resonators’ position on the wafer. Third, we demonstrate how curve fitting of loss and coupling coefficients as a function of the gaps can be used to estimate the optimal gap that realizes critical coupling with a significantly reduced number of manufactured test structures needed to find optimal design parameters.